2016
DOI: 10.1002/cphc.201500839
|View full text |Cite
|
Sign up to set email alerts
|

Noncovalent Interaction of Graphene with Heterocyclic Compounds: Benzene, Imidazole, Tetracene, and Imidazophenazines

Abstract: Noncovalent functionalization of graphene with organic molecules offers a direct route to multifunctional modification of this nanomaterial, leading to its various possible practical applications. In this work, the structures of hybrids formed by linear heterocyclic compounds such as imidazophenazine (F1) and its derivatives (F2-F4) with graphene and the corresponding interaction energies are studied by using the DFT method. Special attention is paid to the hybrids where the attached molecule is located along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 45 publications
3
18
0
Order By: Relevance
“…Solomon and co‐workers [ 52 ] reported that noncovalent π–π stack between SLG and aromatic (benzene, anthracene) anchor can efficiently suppress phonon transport, leading to smaller phononic thermal conductance by an order of magnitude than that in the analogous junction with CC covalent contact at 300 K. The amine–SLG interaction (0.22 eV) is fivefold weaker than the π–π stack (1.01 eV), making our reasoning plausible. [ 27,53 ] Such a difference in the temperature drop between the covalent and noncovalent contacts is not trivial but cannot fully account for our observations. Our experiments (discussed below) indicate that the electronic structural effect contributes significantly to the observed difference in S values between SLG//H 2 NC n and Au/SC n SAMs.…”
Section: Resultsmentioning
confidence: 82%
“…Solomon and co‐workers [ 52 ] reported that noncovalent π–π stack between SLG and aromatic (benzene, anthracene) anchor can efficiently suppress phonon transport, leading to smaller phononic thermal conductance by an order of magnitude than that in the analogous junction with CC covalent contact at 300 K. The amine–SLG interaction (0.22 eV) is fivefold weaker than the π–π stack (1.01 eV), making our reasoning plausible. [ 27,53 ] Such a difference in the temperature drop between the covalent and noncovalent contacts is not trivial but cannot fully account for our observations. Our experiments (discussed below) indicate that the electronic structural effect contributes significantly to the observed difference in S values between SLG//H 2 NC n and Au/SC n SAMs.…”
Section: Resultsmentioning
confidence: 82%
“…36 However, the earlier literature on adsorption of N-heterocycles did not report anything about the involvement of N–H···π interactions. 10 In the case of complexes with doped Cor, d N–H···π is decreased with an increase in the number of N in the heterocyclic ring (especially for Tetra and Penta), suggesting the key role of N–H···π interaction in stabilizing their complexes, Table 1. For example, in the case of complexes involving Cor (3N) , d N–H···π decreases in the following order: Cor (3N) -Im (2.90) > Cor (3N) -Pz (2.78) > Cor (3N) -Pyr (2.77) > Cor (3N) -123-tria (2.75) > Cor (3N) -124-tria (2.73) > Cor (3N) -Tetra (2.65) > Cor (3N) -Penta (2.44); values are in angstrom.…”
Section: Results and Discussionmentioning
confidence: 99%
“…9,10,12 Zarudnev et al have reported the SE value of 7.90 kcal mol –1 for adsorption of Im on graphene (obtained at the M05-2X/6-31++G(d,p) level of theory) surface. 10 Although Im and Pz are isomeric/isoelectronic, SE values are relatively higher for Cor-Pz complexes (which may be attributed to the higher contribution from the N–H···π interaction, as evident from the N–H···π distance). This validates the importance of the position of N in the heterocycles in stabilizing the complexes.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As aforementioned, nevertheless, either the substituent effect is attributed to π ‐ polarization or to local interaction, the substituent effects have been mostly rationalized with help of supermolecular approaches, and the role of substituents has been indirectly guessed from binding energy . Due to the size of the small stacked models, the hydrogens of the other ring may play role, as noticed by Rashkin and Waters .…”
Section: Introductionmentioning
confidence: 99%